Preparation Formulationlip Creamhenry Leaf Extract (Lawsonia Inermisl) As A Natural Dye - Febi Arsita Safitri; Evi Mustiqawati; Restu Harisma Damayanti (Journal of Health Science and Pharmacy, 2026)
Background: Indonesia possesses abundant plant resources with significant potential for use as natural ingredients in cosmetic products, one of which is henna leaves (Lawsonia inermis L.). Henna leaves contain natural orange pigments that can be utilized as colorants. The distinctive orange hue of henna makes it a promising natural dye for decorative cosmetic products, particularly lip cream formulations, as an alternative to synthetic dyes. Objectives: This study aimed to formulate a lip cream preparation using henna leaf extract as a natural colorant and to evaluate the physical properties of the resulting formulations. Methods: Henna leaf extract was obtained through the maceration method using 70% ethanol as the solvent. The extract was then formulated into lip cream preparations with three different concentrations: F1 (2%), F2 (4%), and F3 (6%). Physical evaluation of the lip cream included organoleptic assessment, homogeneity test, spreadability test, and pH measurement. Results: The organoleptic evaluation showed that all formulations produced a brown-colored lip cream with a semi-solid consistency. Homogeneity testing indicated that all formulations were homogeneous. The pH values of F1, F2, and F3 were within the acceptable range for lip cream preparations. However, the spreadability test results revealed that none of the formulations met the specified requirements. Conclusion: Henna leaf extract demonstrates potential as a natural colorant in lip cream formulations. Nevertheless, further formulation development is required to improve the spreadability characteristics to achieve optimal physical quality of the product. Keywords: Henna Leaves, Formulation, Lip Cream, Natural Colorant